Speaking up about safety concerns: multi-setting qualitative study of patients' views and experiences. Issue 6 (25th September 2012) - Entwistle, Vikki A; McCaughan, Dorothy; Watt, Ian S; Birks, Yvonne; Hall, Jill; Peat, Maggie; Williams, Brian; Wright, John
Abstract : Objectives: To explore patients' and family members' experiences of and views about speaking up about safety concerns at the point of care. Design: Qualitative study using 71 individual interviews and 12 focus group discussions. Participants and settings: People with recent experience of one of five conditions or interventions associated with different safety problems (childhood asthma, diabetes, breast cancer, elective joint replacement and severe and enduring mental health problems) and people who had lodged concerns with healthcare providers were recruited from both NHS services (primary and secondary care) and patient support organisations. Findings: Participants had identified various safety concerns in the course of their healthcare and had sometimes spoken up about these as they occurred. Their inclination and ability to speak up were apparently variously shaped by their assessments of the gravity of the threat of harm, the relative importance of their concern given other patients' needs and staff workloads and priorities, their confidence about their grounds for concern, roles and responsibilities and the likely consequences of speaking up. These assessments were pervasively influenced by the way healthcare staff behaved and related to them. People who had spoken up about concerns reported diverse responses from health professionals. Some responses averted harm or provided welcome reassurance, but others exacerbated anxieties and possibly contributed to patient harm. Conclusion: The potential for patients to contribute to their safety by speaking up about their concerns depends heavily on the quality of patient–professional interactions and relationships.